(untitled) (GEOmedia, 2016)
Among the creation of geomorphological maps the data collection of elements and features is one of the most important steps. The most relevant information to be collected are not only their position (geolocalization) but also their classification and properties according to the official encoding: within this context the Italian National Geologic Service (SGN) set up data collection and data storing standards through a focused documentation, the "I Quaderni” (series III), n.4 e n.10. In this paper we describe a new system to collect these kind of data directly on the field through the most commonly used tablets and smartphones. This system is based on an ESRI Geodatabase Enterprise installed on a server, an ArcGIS Online account and the ESRI Collector App for smartphones. Data collected by operators on the field are directly sent to the Geodatabase on server using mobile internet connection; data structure and format follow the national standards, so they are ready to be added into a geomorphological map.